2023
DOI: 10.3390/healthcare11152139
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Fracture Incidence in Germany: A Comparative Age and Gender Analysis of Pre- and Post-Outbreak Periods

Abstract: In March 2020, Germany imposed a nationwide lockdown to curb the spread of COVID-19, prompting questions about the impact on the incidence of common fractures. This study examined 15 fracture types in pre-outbreak (2010–2019) and post-outbreak (2020–2021) periods, using data categorized by age (18–64 years, >65 years) and sex (male, female). Linear regression assessed annual growth rates, and mean fracture numbers were compared across periods for significant differences. Results indicated a positive correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…It was also observed that during the COVID-19 pandemic older people more frequently experienced low-energy injuries (due to falls or slips) ( Gawronska & Lorkowski, 2021 ). Similar findings were reported by researchers who investigated the effect of COVID-19 on the incidence of fractures in Germany, and observed a higher incidence of fractures after the outbreak of the pandemic ( Heinz et al, 2023 ). A study has also shown that patients with stroke combined with COVID-19 present poorer functional performance compared to non-COVID-19 patients with stroke ( Ntaios et al, 2020 ).…”
Section: Introductionsupporting
confidence: 89%
“…It was also observed that during the COVID-19 pandemic older people more frequently experienced low-energy injuries (due to falls or slips) ( Gawronska & Lorkowski, 2021 ). Similar findings were reported by researchers who investigated the effect of COVID-19 on the incidence of fractures in Germany, and observed a higher incidence of fractures after the outbreak of the pandemic ( Heinz et al, 2023 ). A study has also shown that patients with stroke combined with COVID-19 present poorer functional performance compared to non-COVID-19 patients with stroke ( Ntaios et al, 2020 ).…”
Section: Introductionsupporting
confidence: 89%
“…It began on March 11, 2020 and ended on May 5, 2023 by the World Health Organization (Baloch et al, 2020;Ciotti et al, 2020;Souto, 2020). In addition to the direct impact of the disease, the health system faced a series of unprecedented logistical and care challenges (Alencar et al, 2022;Silva et al, 2022;Heinz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%